Assessing the risk of false positive serum galactomannan among patients receiving piperacillin/tazobactam for febrile neutropenia. (25th November 2016) - Demiraslan, Hayati; Atalay, M. Altay; Eren, Esma; Demir, Koray; Kaynar, Leylagul; Koc, A. Nedret; Doganay, Mehmet
Abstract: Galactomannan (GM) assay is commonly used as an early diagnostic tool for invasive fungal infection (IFI) in high-risk hematology patients. False positivity is frequently observed in GM with the use of piperacillin/tazobactam. The usage of generic drugs over the original brand has a significant cost advantage. The aim of this study was to assess the performance of GM test among patients receiving original and generic piperacillin/tazobactam formulations. The study included 85 adult patients; 62.4% were male with hematological malignancy currently receiving piperacillin/tazobactam. The study group was divided into two groups: patients receiving original and generic piperacillin/tazobactam. Serum GM index was positive in one of 35 patients receiving original piperacillin/tazobactam, whereas it was positive in 46 out of 50 patients receiving generic piperacillin/tazobactam ( P < .001). However, the patients receiving generic piperacillin/tazobactam underwent computed tomography (CT) scans more frequently than those receiving original piperacillin/tazobactam ( P = .047). In addition, in vitro analysis of GM was performed in two generics and one original piperacillin/tazobactam vials. One generic piperacillin/tazobactam vial included high GM level. False positivity of serum GM with generic formulations of piperacillin/tazobactam is still an ongoing issue in hematology patients. A high rate of serum GM index false positivity may unexpectedly lead to a higher rate of CT scan. Selected piperacillin/tazobactam vials in each batch should be checked for GM to identify a false positivity of GM before purchase.